2009 3rd International Conference on Affective Computing and Intelligent Interaction and Workshops 2009
DOI: 10.1109/acii.2009.5349473
|View full text |Cite
|
Sign up to set email alerts
|

Foundations for modelling emotions in game characters: Modelling emotion effects on cognition

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…According to Hudlicka (2009), Hudlicka and Broekens (2009) and Conati and Zhou (2002), in order for games to be effective and realistic, game characters should possess emotional reactions such as embarrassment and body language including facial expressions, head and hand movement. The emotional variables need to affect the characters' decision making and behavior during the game leading to changes in facial expressions or body movements (Huldicka, 2009).…”
Section: Emotions and Learningmentioning
confidence: 99%
“…According to Hudlicka (2009), Hudlicka and Broekens (2009) and Conati and Zhou (2002), in order for games to be effective and realistic, game characters should possess emotional reactions such as embarrassment and body language including facial expressions, head and hand movement. The emotional variables need to affect the characters' decision making and behavior during the game leading to changes in facial expressions or body movements (Huldicka, 2009).…”
Section: Emotions and Learningmentioning
confidence: 99%
“…[9][10][11] Popescu et al 9 stated that if an emotional aspect were present in nonplayer characters, there would be an increase in the variations of characters' behavior that could create more interesting games. Hudlicka and Broekens 11 showed that focusing on producing more believable virtual characters in games by using emotions would be a step toward more engaging games, both for entertainment and serious gaming purposes. Computational models of emotion are usually based on psychological emotion theories and attempt to model the rules of the theories.…”
Section: Emotion Modeling In Gamesmentioning
confidence: 99%
“…Initial studies on modelling the behaviour of the player and how to design adaptive videogames were performed by Charles et al [75] and Sykes and Federoff [76] in 2005 and 2006, respectively. On the other hand, Hudlicka [77], Hudlicka and Broekens [78], Hudlicka [79] performed a deep study on how to model emotions and improve the consistency between it and gaming architectures. The papers then discusses how these computational building blocks can provide a basis for the development of more systematic guidelines for affective model development.…”
Section: Gameplay and Adaptationmentioning
confidence: 99%
“…Charles et al [75], Sykes and Federoff [76] Initial studies on adaptive game design Hudlicka [77], Hudlicka and Broekens [78], Hudlicka [79] Design guidelines to emotion modelling Baharom et al [80,81] Conceptual framework of emotional design Shaker et al [82,83] Dataset: game events and recorded video sessions Pereira et al [84] Contagion of emotions between nonplayable characters Furthermore, Shaker et al [82,83] published an interesting approach in 2011: a dataset of game events and recorded video sessions from human players while playing a videogame. This dataset can be used by other researchers to analyse the relationship between the game context and the players' behaviour and affective state.…”
Section: Paper(s) Topicmentioning
confidence: 99%